Visually Spreading the Message: Da'wah Through Illustration in Peduli Jilbab Community - Septiana, Wilujeng Eky; Rahina Nugrahani; Tjetjep Rohendi Rohidi (Catharsis, 2024)
This study explores the role of Muslim women in spreading Da'wah through visual illustrations within the Peduli Jilbab Community on social media. The research addresses the need to understand how religious values and visual arts intersect to promote Islamic teachings. Employing a qualitative approach guided by Rohidi (2011), the study aims to systematically describe and analyze the involvement of Muslim women in religious outreach via digital illustrations. Data were collected through participant observation, interviews, documentation, case studies, and Focus Group Discussions (FGDs). The interdisciplinary methodology integrates virtual ethnography, aesthetics, and Islamic values, examining digital illustrations when online interactions became crucial. The study involved 129 members selected through social media outreach and community gatherings. Results indicate that visual illustrations effectively convey religious messages, enhance personal faith, and engage a broader audience. The findings highlight the potential of combining art and Da'wah, offering insights into innovative methods of religious outreach in the digital age. These implications underscore the importance of supporting creative expressions of faith and fostering inclusive, virtual communities for religious education.